Thermoluminescence Study of Y2O3: Tb - Brahme, Nameeta; Gupta, Anuradha; Bisen, D P; Kurrey, U (Recent Research in Science and Technology, 2012)
Nanophosphors were prepared by the combustion technique using yttria and terbia powder as precursors and urea as fuels. The particle is investigated by X-ray diffraction analysis. X-ray diffraction patterns confirm the formation of pure cubic phase of Y2O3 .The resulting product was characterized by FTIR spectra to evaluate the vibrational feature of the sample. TL emission spectra show intense peak around 520 nm.